Calculated and observed long term performance of Leneghans embankment - Manivannan, G.; Karim, M.R.; Gnanendran, C.T.; Lo, S.C.R. (2011)
This paper presents the finite element (FE) analysis of the consolidation of the foundation of an embankment constructed over soft clay deposit which shows significant time dependent behaviour and was improved with prefabricated vertical drains. To assess the capability of a simple elastic viscoplastic (EVP) model to predict the long term performance of a geotechnical structure constructed on soft soils, a well documented (Leneghans) embankment was analyzed to predict its long term behaviour characteristics. Two fully coupled two dimensional (2D) plane strain FE analyses have been carried out. In one of these, the foundation of the embankment was modelled with a relatively simpler time dependent EVP model and in the other one, for comparison purposes, the foundation soil was modelled with elasto-plastic Modified Cam-clay (MCC) model. Details of the analyses and the results are discussed in comparison with the field performance. Predictions from the creep (EVP) model were found to be better than those from Elasto-plastic (MCC) analysis. However, the creep analysis requires an additional parameter and additional computational time and resources.